Whatsapp Voice Note in Speaking Class - Hega Nurazizah; Lilies Youlia Friatin; Bambang Ruby Sugiarto (Universitas Bengkulu, 2019)
This study deals with the use of WhatsApp voice note in speaking class. This study aimed at figuring out the teacher’s way in implementing WhatsApp voice note in teaching speaking on narrative text and investigating the perspective on WhatsApp voice note to improve speaking skill on narrative text. In conducting this study, the researcher used qualitative approach. Case study was applied as a research design in this study. This study involved 35 students of the tenth grade (X MIPA 1) and one English teacher. Instruments used in this study were classroom observation, interview, and questionnaire. The results of this study showed that nine steps were used by the teacher in the teaching and learning process through WhatsApp voice note in speaking class on narrative text. Meanwhile, most of the students gave their positive response toward the teaching and learning process. The teacher argued that WhatsApp voice note is a useful tool to provide the students opportunities to speak especially on narrative text and the students can share information easily. It also allows the students asking for help using English. Based on the findings, it can be concluded that learning to speak English using WhatsApp voice note is an attractive learning activity, positive activity, and WhatsApp voice note is easy to use. Finally, this study suggests other researchers to involve the objective data, to enrich the instrumentation, to add more sample of the study and to employ other methods and design in order to enrich the data.